2013
DOI: 10.7763/ijcte.2013.v5.818
|View full text |Cite
|
Sign up to set email alerts
|

The Tendency for Using Accounting Information Systems in Lebanese Firms

Abstract: Abstract-The purpose of this study is to show the impact of Accounting Information System (AIS) on accounting in Lebanese companies. There are many advantages of AIS, yet there are many disadvantages too. One must check an AIS affordability, time saving, additional costs, cash saving, and employees' adaptation. In this research, quantitative study is done in which questionnaires are filled by accountants and accounting managers to see how this community looks to AIS, how it affects accounting, its positive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Therefore, the use of AIS has a great impact on the improvement of the decision-76 making process, internal control, and performance assessment. Moreover, it has been found that AIS are important and have a highly positive impact on OP (David Naranjo-Gil, 2009;Pierre et al, 2013;Al-dmour et al, 2017;Fadzilah, 2017;Kanakriyah, 2017;Rasit & Ibrahim, 2017;Susanto & Meiryani, 2019). In order to understand the effects of using AIS, the researchers formulated the following hypothesis: H1: The use of AIS has a positive influence on organizational performance.…”
Section: Hypotheses Development In the Ais Domainmentioning
confidence: 99%
“…Therefore, the use of AIS has a great impact on the improvement of the decision-76 making process, internal control, and performance assessment. Moreover, it has been found that AIS are important and have a highly positive impact on OP (David Naranjo-Gil, 2009;Pierre et al, 2013;Al-dmour et al, 2017;Fadzilah, 2017;Kanakriyah, 2017;Rasit & Ibrahim, 2017;Susanto & Meiryani, 2019). In order to understand the effects of using AIS, the researchers formulated the following hypothesis: H1: The use of AIS has a positive influence on organizational performance.…”
Section: Hypotheses Development In the Ais Domainmentioning
confidence: 99%
“…Wongsim and Gao (2011) stated that AIS is a specific software application and management process. Pierre et al (2013) defined AIS as a computerized system that collects, inputs, and processes data, in addition to storing, managing, controlling, and reporting information that can be used in different tasks such as planning and decision making. Overall, computerized AIS in this study can be defined as the application of the computer-based software to input financial data, process them, and thereafter output financial information ( Fig.…”
Section: Computerized Aismentioning
confidence: 99%